Kill, incarcerate, or liberate? Ethics and alternatives to orangutan rehabilitation - Palmer, A (Elsevier, 2018)
Despite its high cost and debatable conservation value, orangutan rehabilitation and reintroduction (R&R) continues. Drawing on qualitative research with orangutan conservationists, this paper argues that a central reason why R&R practitioners undertake this activity is a view that the alternatives, killing orangutan orphans or keeping them in captivity, are practically or ethically unacceptable. However, questions remain over whether orphans might be better off in captivity than in the wild, and why orphans appear to attract more attention and support than wild orangutans. In evaluating these questions, practitioners must weigh up obligations to individuals and larger units, displaced and wild orangutans (the former visible, and the latter abstract), and properties of orangutans such as their wildness, welfare, and autonomy. As advocates of compassionate conservation have highlighted, similar ethical dilemmas arise in the conservation of other species.